After two decades of halal consumer research: is there a future for aquaculture discipline? - Mustafa, Hasri; Ahmi, Aidi (Universiti Malaysia Sabah (UMS), 2023)
This paper aims to understand how scholarly research shaped the aquaculture field since the early 2000s, by taking into consideration the academic literature on halal consumers. We conducted a bibliometric analysis of halal consumer to the aquaculture research discipline by examining the types of documents, style of language used, subject areas, most-cited authors, papers and authors’ keywords to draw a general picture of the field. Our results showed that the halal consumer research has been largely designed based on business, management, and accounting disciplines. Nevertheless, since 2019 these disciplines were approaching their maximum limit as evidenced from our findings. Thus, as the field of halal consumer research in these disciplines are ‘matured’, we view the next most influenced subject areas, the disciplines of agricultural and biological sciences, as the future potential winners in the halal consumer research. Our bibliometrics sets a baseline that will enable scholars to foresee how the field of aquaculture research and halal consumer could directly inform each other in establishing a new area of halal consumer-aquaculture research.